2018
DOI: 10.1097/ncc.0000000000000487
|View full text |Cite
|
Sign up to set email alerts
|

Change of Uncertainty in Illness and Unmet Care Needs in Patients With Recurrent Hepatocellular Carcinoma During Active Treatment

Abstract: Healthcare providers should take into account each individual's age, levels of psychological need, and symptom distress and should offer personalized information related to psychological needs and symptom management to decrease levels of uncertainty before discharge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…( 30 , 32 ) Higher levels of depression are associated with higher rates of unmet supportive needs and uncertainty about illness, and rates of suicidality tend to be higher among patients with cirrhosis than the general population. ( 46 , 47 , 48 ) Patients with AdvLD and their caregivers note major disruptions in their personal and family lives, particularly as their illnesses worsen. ( 30 , 32 , 49 ) Major social burdens faced by patients include financial costs, limited social support, active or former substance use, stigma of having liver disease, impaired sexual health, and perceived burden on other family members.…”
Section: Resultsmentioning
confidence: 99%
“…( 30 , 32 ) Higher levels of depression are associated with higher rates of unmet supportive needs and uncertainty about illness, and rates of suicidality tend to be higher among patients with cirrhosis than the general population. ( 46 , 47 , 48 ) Patients with AdvLD and their caregivers note major disruptions in their personal and family lives, particularly as their illnesses worsen. ( 30 , 32 , 49 ) Major social burdens faced by patients include financial costs, limited social support, active or former substance use, stigma of having liver disease, impaired sexual health, and perceived burden on other family members.…”
Section: Resultsmentioning
confidence: 99%
“…Two studies (Gillespie et al, 2017;Shun et al, 2018) reported the presence of unmet needs of patients with rare digestive cancer.…”
Section: Unmet Needs Of Patients With Rare Digestive Cancermentioning
confidence: 99%
“…In the diagnostic phase, predictive factors associated with a higher number of unmet needs in patients with rare cancers included higher neuroticism, lower instrumental social support and greater social network (Williamson et al, 2018). Predictive factors for unmet needs during treatment and posttreatment phase were somewhat inconsistent and included both younger age (Shun et al, 2018) and older age (V.L. Beesley et al, 2013), but also higher anxiety score (V.L.…”
Section: Predictive Factors For Unmet Needs Throughout the Rare Cancer Disease Trajectorymentioning
confidence: 99%
“…Uncertainty in illness refers to a state of doubt and uncertainty caused by the lack of effective cognition of a disease and the lack of control over disease-related situations. It can lead to psychological states such as fear, and an increase in the psychological burden of patients, which can then affect the process of treatment [ 3 , 4 ]. Coping is a kind of cognitive behaviour that patients may use to relieve their psychological stress.…”
Section: Introductionmentioning
confidence: 99%